2018
DOI: 10.1044/2018_jslhr-l-18-0008
|View full text |Cite
|
Sign up to set email alerts
|

A Multimethod Analysis of Pragmatic Skills in Children and Adolescents With Fragile X Syndrome, Autism Spectrum Disorder, and Down Syndrome

Abstract: Purpose Pragmatic language skills are often impaired above and beyond general language delays in individuals with neurodevelopmental disabilities. This study used a multimethod approach to language sample analysis to characterize syndrome- and sex-specific profiles across different neurodevelopmental disabilities and to examine the congruency of 2 analysis techniques. Method Pragmatic skills of young males and females with fragile X syndr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
41
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(49 citation statements)
references
References 86 publications
7
41
1
Order By: Relevance
“…Pragmatic language differences have been repeatedly observed among PM carriers (27,57,(100)(101)(102), and were evident in this study as well, with additional patterns noted across the types of pragmatic language violations occurring more frequently in the PM group, who tended to display a more dominant conversational style (e.g., overly detailed, tangential language) than controls. Differences in pragmatic language have consistently emerged as a phenotypic marker associated with the PM in females (27,(100)(101)(102), and among individuals with FXS, particularly those who meet criteria for ASD (62,(103)(104)(105)(106)(107)(108)(109) and may be of clinical importance. For instance, prior work has shown that pragmatic language violations among mothers of children with FXS were associated with reduced selfreported quality of life for mothers (102), as well as elevated ASD symptoms and weaker expressive and receptive language in their children (27,100).…”
Section: Discussionmentioning
confidence: 99%
“…Pragmatic language differences have been repeatedly observed among PM carriers (27,57,(100)(101)(102), and were evident in this study as well, with additional patterns noted across the types of pragmatic language violations occurring more frequently in the PM group, who tended to display a more dominant conversational style (e.g., overly detailed, tangential language) than controls. Differences in pragmatic language have consistently emerged as a phenotypic marker associated with the PM in females (27,(100)(101)(102), and among individuals with FXS, particularly those who meet criteria for ASD (62,(103)(104)(105)(106)(107)(108)(109) and may be of clinical importance. For instance, prior work has shown that pragmatic language violations among mothers of children with FXS were associated with reduced selfreported quality of life for mothers (102), as well as elevated ASD symptoms and weaker expressive and receptive language in their children (27,100).…”
Section: Discussionmentioning
confidence: 99%
“…Such comparisons can inform our understanding of how ASD impacts language, and whether uniquely tailored language interventions may be needed for these clinical groups (Abbeduto & Murphy, 2004). However, studies comparing the expressive language profiles of the two groups have been limited, and results have been inconsistent, partially as a reflection of different assessment methods being utilized (Haebig & Sterling, 2017; Klusek et al., 2014b; Martin et al., 2018; Sterling, 2018; Thurman et al., 2017). Thus, the purpose of the present study was to compare the expressive language profiles of boys with FXS + ASD and boys with idiopathic ASD, and to examine whether a similar linguistic profile emerged across two different language sampling contexts that are commonly used in the literature (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, an increasing number of studies have begun to use other assessment tools, such as the Autism Diagnostic Observation Schedule (ADOS, ADOS-2; Lord et al., 1999, 2012), to examine the language abilities of children with FXS and ASD (e.g. Estigarribia, et al., 2011; Klusek et al., 2014b; Martin et al., 2018; Park et al., 2012; Roberts et al., 2007a). Indeed, Tager-Flusberg and expert colleagues (2009) noted the value of using multiple language samples in the assessment process, and recommended the ADOS as a way to collect natural language samples in children with ASD.…”
Section: Language Sampling Methods: Using the Autism Diagnostic Obsermentioning
confidence: 99%
See 1 more Smart Citation
“…Most males and many females with FXS have impaired communication (Abbeduto et al, 2016). Impairments have been reported in the areas of speech intelligibility (Barnes et al, 2009), vocabulary (Roberts et al, 2007;Sudhalter & Belser, 2001), morphology and syntax (Komesidou et al, 2017;Martin et al, 2013), and pragmatics (Martin et al, 2018). In addition, individuals with FXS have impaired cognition, and there is a relationship between the amount of impairments in cognition and communication (Abbeduto et al, 2007;Oakes et al, 2013).…”
Section: Language Development In Fxsmentioning
confidence: 99%